THE EFFECTIVINESS OF DYADIC COPING SKILL TRAINING ON COPING, MARITAL SATISFACTION, AND PSYCHOLOGICAL ADJUSTMENT AMONG CANCER PATIENTS - Nurul Huda; Jumaini Jumaini; Erwin Erwin; Ayuro Cumayunaro; Dwi Kartika Rukmi (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2026)
Introduction :Cancer diagnosis and the treatmet that must be carried out sometimes make the patients experience the psychological problem and less satisfaction in marriage. It does not only impact the patients but also their life partner. Therefore during the treatment period, the patients and their spouse are seen as one unity that influences each other. Dyadic coping is a coping formed altogether with the patients which emphasizes more on the interaction among the spouses and proven more effective in annuling the stressors. Purpose : The purpose of this research was to see the effectiveness of dyadic coping skill training intervention in cancer patients and their spouse in increasing the coping, marriage satisfaction, and psychological adjustment. Method :This research employed conceptual framework named The Systematic Transactional Model by Bodenmann. This research was a quantitative research with quasi experimental pre and post test design. The participants in this research were cancer patients and their spouse who were taking the therapy at Public Regional Hospital, Riau Province. The participants were selected by using purposive sampling based on the inclusion criteria. Total participants were 17 patients. The research instruments used in this research covered Dyadic Coping Inventory, Dyadic Adjustment Scale, and Benefit Funding Scale Indonesian Version which had been validated. Results : The analysis result showed that there was change of the average of dyadic coping score (p0.001), marriage satisfaction (p0.001), and psychological adjustment (p0.001) in patients who had been given intervention of dyadic coping skill training. Discussion : This research proved that dyadic coping skill training intervention was effective in increasing the couple coping, marriage satisfaction, and psychological adjustment until it can be made as one holistic nursing intervention towards the patients’ cancer.